(untitled) (Journal of actual problems of jurisprudence, 2016)
The article deals with the outstanding figure in the history of the Kazakh people of Abul Khair Khan. Scientifically described state activity Khan Junior Juz Abulhair, as well as political, diplomatic, military positions during the era of Khan. Considered various military and diplomatic methods. Defines the role and place of Khan politics of neighboring states.